Comparision of Efficacy of Amoxicillin and Ciprofloxacin in Clean Contaminated Ear Surgery During Early Post Operative Period - Chapagain, Kumud; Pokharel, Rais; Kafle, Kumud Kumar; Sinha, Bimal Kumar (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To compare the efficacy of amoxicillin and ciprofloxacin used in clean contaminated ear surgery during the early post operative period. Materials and Methods: It is a longitudinal, prospective study conducted at Department of Otorhinolaryngology and Head and Neck Surgery, TUTH from 1st April 2011 to 30th December 2011. Patient who underwent clean contaminated ear surgery were followed up on 1st, 3rd and 7th post – operative day (POD) and wounds were inspected for any signs of wound infection. Results: 103 patients who under went various clean contaminated ear surgeries were included in this study. Maximum patients were aged 14-29 years. Ciprofloxacin was prescribed to 80 (77.7%) patients and amoxicillin to 23 (20.3%) patients. Overall wound infection was present on 6.2% (5/80) patients receiving ciprofloxacin and on 4.34% (1/23) patients receiving amoxicillin. The most common procedure performed was MRM (53%). Wound infection was present in 9% (4/44) of patients undergoing MRM under coverage of ciprofloxacin and on 9% (1/11) patients under coverage of amoxicillin. Conclusion: Though the rate of wound infection was more in patient using ciprofloxacin than amoxicillin but it was not statically significant. Nepalese Journal of ENT Head and Neck Surgery, Vol. 5, No. 2, 2014, page: 8-10